Single Parent Communication Patterns in Forming Child Independence in Medan City - Abrar Adhani (International Journal Reglement & Society (IJRS), 2023)
One of the factors that influence children's independence is parenting style. Parenting style includes the process of educating, guiding, disciplining and protecting children to reach maturity in accordance with the norms in society. Divorce or death of a partner is something that cannot be avoided in the family. This often has a big impact on family life. The type of research used is qualitative research with a descriptive approach. The data analysis technique used in this research is to describe the research results obtained from the interview results. begins with data reduction which is carried out by selecting data, simplifying data, abstracting, and transferring raw data that emerges from written notes in the field then presenting the data by interpreting it descriptively. Communication patterns used by single parents can be categorized into linear, interaction and transaction. Several situations encountered in everyday life encourage the use of different communication patterns. Thus a single parent can use more than one communication pattern. The three types of communication patterns used by single parents can actually shape children's independence although at different levels. The term single parent is often used to refer to mothers who have a single parent role because most children whose parents are divorced are in the care of a mother. In addition to supporting and facilitating children, parents also need to give responsibility to them according to their abilities, this aims to build children's independence from an early age.